Redesign Process to Improve Enrollment Faculty of Administrative National University of San Marcos - Narciso Gómez, Kennedy (2017)
Deliverable value of this research is to implement the methodology is an adaptation of the approach called systematic redesign, where we have identified existing processes that have been reviewed systematically to propose new process in order to improve services to new entrants of undergraduate enrollment in the Faculty of Management integrated the Single System of registration of San Marcos.Redesigning processes will improve registration services, promoting a new way of operating in the Single Registration System (SUM) in quality services to students; in other words, it allows changing attitudes, values and organizational culture because concentrate its investments in the capacity of their resources and skills of their human strength, to create a differentiated and sustainable value.